Photocatalytic activity of spectro-pure titanium dioxide: Effects of crystalline structure, specific surface area and sorption properties - Evgeny I. Kapinus; Tatyana A. Khalyavka; Valentina V. Shimanovskaya; Tatyana I. Viktorova; Vladimir V. Strelko (International Journal of Photoenergy)
Dispersed optically pure anatase, rutile and two-phase samples of titanium dioxide were prepared using a sol-gel technique. In particle of two-phase samples, the anatase nuclei are surrounded by a rutile envelope. Content of anatase in the two-phase particles varied between 20 and 80%. Particles of all the TiO2 samples had a globular shape of diameter between 10 and 30 μm. When compared to the corresponding technical-grade samples, the optically pure anatase and rutile demonstrated higher photocatalytic activity in the destruction of tetradecylpyridinium chloride, Methylene Blue and tetrachlorofluorescein as well as in reduction of Cr2O7, MnO4, [Fe(CN)6]3− and [Fe(CN)6]4−. The photocatalytic reactions bring about the reduction of the inorganic anions to yield water insoluble substances and mineralization of the organic compounds. Rate constant of the all above processes do not depend on specific surface area of TiO2 and adsorption of the substrates on the TiO2 samples. The rutile calcined at 1027K exhibits the highest specific rate constants. Exposure to γ-radiation increases photocatalytic activity of the dispersed TiO2. The influence of TiO2 and substrate on the photocatalytic reactions is caused by the influence of these factors on the formation of reactive electron hole pair and on the efficiency of the interfacial electron transfer.